Membership service specifications for safety-critical geocast in vehicular networks. - CAHILL, VINNY; BOUROCHE, MELANIE (IEEE, 2010)
Geographic group communication is a promising technique for collaborative driving applications. While oneway, geographic broadcast (geocast) is well-studied in vehicular networks, there has been little work to address the challenging reliability problems that arise. Not only do vehicular networks experience highly variable packet loss, but communication failures are difficult to detect. The presence of vehicles in an area and thus the set of vehicles that is supposed to receive a geocast, changes continuously. Without an expectation of the vehicles that should respond to queries, communication failure cannot easily be distinguished from absence. This requires a cross-layer approach, exploiting communication, sensing and driving rules. In this paper, we propose a membership service that provides group views for geographic areas as a building block to reliable geocast. We specify the semantics of the service and discuss different ways of implementing it. Finally, we show how it can be used for safe, collaborative driving.
Proceedings of the Seventh IEEE, IET International Symposium on Communication Systems, Networks and Digital Signal Processing (CSNDSP)
IET International Symposium on Communication Systems, Networks and Digital Signal Processing (CSNDSP),
PUBLISHED
.
Keywords: traffic engineering computing; Inter-Vehicle Communication, Reliable Broadcast; Smart & Sustainable Planet